KONTRIBUSI 'URF DALAM PENGEMBANGAN FIIQH ISLAM - Ayoeb Amin (Unissula, 2005)
Allah sent dawn the revelation, that is Qur'an and Sunnah as law resources in Islam. Fiqh is the results of the interpretation for texts of the Qur'an and Sunnah. Man who interpreted such texts of the Qur'an and Sunnah was under the influence of the several factors, among others 'urf. The 'urf is the basis of law enforcement, which is not mentioned in the Qur'an and Sunnah. The 'urf plays agreat role in law enforcement, especially in the muamalah duniawiyah. Therefore, the 'urf makes a significant contribution to the Islamic fiqh development.